Compressive Osseointegration of Tibial Implants in Primary Cancer Reconstruction - O’Donnell, Richard J. (Springer-Verlag, 2009)
Compressive osseointegration technology, which provides immediate, mechanically compliant endoprosthetic fixation, has been adapted for massive proximal tibial reconstructions in an attempt to avoid aseptic failure encountered with conventional stems. A retrospective review of 16 patients with resected tumors was undertaken to determine whether compressive osseointegration can provide durable anchorage of tibial implants. Medical records, radiographs, and clinical examinations were reviewed to assess surgical, local disease control, and prosthetic outcomes. The average age was 18 years (range, 12–42 years). Diagnoses included osteosarcoma (12), Ewing sarcoma (two), chondrosarcoma (one), and undifferentiated sarcoma (one). Minimum followup was 2 years (mean, 4.5 years; range, 2–10.3 years); no patient was lost to followup. There were no local recurrences. Four patients developed metastatic disease; one patient died of his primary tumor, and another died from a chemotherapy-related malignancy. Complications included one early deep infection that ultimately resulted in prosthetic loosening and the need for an above-knee amputation. There were two late deep infections; prosthetic retention was achieved with débridement and antibiotics. One patient developed aseptic loosening and underwent revision; the other 15 implants provided stable osseointegration at last followup. Compressive osseointegration technology can thus achieve acceptable short-term endoprosthetic fixation results and may reduce the risk of aseptic loosening reported with conventional tibial stems. Level of Evidence: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.